Structural Units of Reovirus Ribonucleic Acid and Their Possible Functional Significance - Watanabe, Y. (1967)
Reovirus contains ribonucleic acid (RNA) equivalent in amount to a molecular weight of approximately 10(7) daltons. On isolation, this RNA is invariably broken into fragments of three different sizes. The three pieces have been separated from each other by chromatography on methylated albumin-kieselguhr columns. Denaturation of the three fragments of RNA in dimethyl sulfoxide led to separation of the strands, as suggested by sucrose gradient sedimentation patterns and by the second-order kinetics of reannealing. Molecular weights of 0.8 × 10(6), 1.4 × 10(6), and 2.4 × 10(6) were determined for the double-stranded fragments from the sedimentation rates of the single-stranded RNA obtained by denaturation. There was little or no homology among the three classes of denatured RNA when taken in pairs in hybridization tests. The three pieces of double-stranded RNA, therefore, did not result from random breaks in the original viral RNA molecule. Virusspecific single-stranded RNA formed in infected cells, and previously found to be largely if not entirely messenger RNA transcribed from the viral genome, was also separated into three size classes by sedimentation through sucrose gradients. Each class of single-stranded RNA corresponded in size to one of the three fragments of double-stranded RNA. The largest piece of single-stranded RNA hybridized uniquely with the largest fragment of denatured viral RNA. By whatever means this fragment of double-stranded RNA may be joined into the viral RNA molecule, it seems to act as a specific unit for transcription of an uninterrupted messenger RNA of equivalent length.